The SEWASIE architecture: a multi-agent system for data integration - Fillottrani, Pablo Rubén (2005)
In this paper we present the SEWASIE system, a multi-level agent-based architecture for querying heterogeneous data sources integrated by means of ontologies. Main features of this system are: two level data integration scheme, a query tool that supports the user in formulating a precise query, integrated tools for negotiation and information monitoring, and an agent infrastructure that provides a unifying framework for the architecture. In this work we focus on the agent infrastructure, from the user interface to the query answering mechanism